Primary hyperparathyroidism: a case report. - Tavares, Joana (2018)
Introduction: The diagnosis of primary hyperparathyroidism may occur incidentally in asymptomatic phases or appear late in the context of nonspecific and prolonged complaints. Case report: We describe the case of a 32-year-old female without relevant previous medical history. In February 2012, she suffered an episode of severe renal colic, requiring nephrostomy. Further investigation identified exuberant renal lithiasis, with indication for a preventive double J catheter. In December 2012, the patient had a rupture of the quadriceps tendon due to a fall, and in March 2013, had a new fall due to imbalance with a resulting fracture of the humeral neck. The patient maintained progressive complaints of back pain, bone and joint pain and generalised muscle weakness, and eventually became wheelchair-dependent in 2014. The patient was referred to the hospital for severe hypercalcemia and raised parathyroid hormone (PTH 4300 pg/ml). Cervical ultrasound and parathyroid scintigraphy confirmed the clinical suspicion of primary hyperparathyroidism due to a parathyroid adenoma. Left parathyroidectomy was performed in May 2014, complicated with a Hungry-Bone syndrome. Clinical and analytical evolution was favorable. Comment: This clinical case seeks to alert to primary hyperparathyroidism as a differential diagnosis when facing non-specific and prolonged osteoarticular complaints. Due to the prevalence of these complaints in clinical practice and the importance of an early diagnosis, the family physician should be alert to this potential diagnosis.